Behavior of dry bean genotypes to Fusarium oxysporum f. sp. phaseoli, Macrophomina phaseolina, and Xanthomonas campestris pv. phaseoli - Maringoni, Antonio Carlos; Lauretti, Renato Luis Bertoni (Pesquisa Agropecuaria Brasileira, 1999)
The behavior of dry bean (Phaseolus vulgaris L.) genotypes PI 150414, PI 163117,PI 175829 white, PI 175829 purple, PI 175858, PI 197687, A 417, A 420, A 429, Xan 160, Xan 161, WISHBR 40, and IAC Carioca inoculated with Fusarium oxysporum f. sp. phaseoli, Macrophomina phaseolina, and Xanthomonas campestris pv. phaseoli was evaluated under greenhouse condition. The bean genotypes Xan 160, PI 150414, A 417, PI 175829 purple, Xan 161, A 420, PI 163117, and PI 175829 white were resistant to F. oxysporum f. sp. phaseoli, and only PI 155829 white had a good level of resistance to M. phaseolina. All bean genotypes were susceptible to Feij-4 strain, and only Xan 161 had some level of leaf resistance to Feij-41 strain of X. campestris pv. phaseoli.